Invited Lectures from the 13th International Congress on Mathematical Education - Kaiser, Gabriele; Forgasz, Helen; Graven, Mellony; Kuzniak, Alain; Simmt, Elaine; Xu, Binyan (ICME-13 Monographs, 2018)
Mathematics Education; Mathematics Learning; Mathematics Teaching; Mathematics Teachers; ICME-13; 13th Congress on Mathematical Education; Empirical Studies in Mathematics Education; Theoretical Reflections on Mathematics Education; Tertiary Mathematics Education; Secondary Mathematics Education; Primary Mathematics Education; Society of Didactics of Mathematics; Mathematics Educators; Improvement of Mathematics Education; Global Mathematics Trends